EVALUATION OF ENVIRONMENTAL LOAD ON FRIUTS AND VEGETABLES CONSUMPTION AND ITS REDUCTION POTENTIAL - AMANO, Koji; SHIMADA, Koji; YOSHIKAWA, Naoki (ENVIRONMENTAL SYSTEMS RESEARCH, 2007)
In this study, we estimated greenhouse gases (GHGs) and acidifying substances (ASs) emissions related to fruits and vegetables consumption in Japan based on lifecycle inventory analysis (LCIA). We also evaluated reduction potential of GHGs and ASs considering the policies of producers and consumers. Total GHGs emission from domestically produced fruits and vegetables in Japan (2003) was nearly 12.7 million tons (CO2 equivalent) in which 65% of the total was from production and 16% was from transportation. GHGs and ASs horn greenhouse crops were higher than those from garden farming crops. Environmental efficiency using the proportion of nutrient content (vitamin C) to the GHGs considering cooking processes was relatively high in mandarin oranges and green peppers growing outside and cabbage. As for the reduction potential, we could evaluate up to 4.8% reduction in lifecycle GHGs emission by optimizing transportation distance (consuming domestic products possibly). This result approximately equals to scenarios of substituting garden farming crops for 20% of greenhouse crops consumption, 20% reduction of food loss, and modal shift. 3.1% we estimated it can be reduced in GHGs by deducting 20% of implementing fertilizers and 16.8% reduction in lifecycle ASs emission by the same reduction of fertilizers, and 7.5% reduction in GHGs emission by introducing heat pump system in greenhouses.